At a very full meeting of delegates from the different counties in the colony and dominion of Virginia : begun in Williamsburg the first day of August, in the year of our Lord 1774, and continued by several adjournments to Saturday the 6th of the same month, the following association was unanimously resolved upon and agreed to ([Printed by Clementina Rind], 1774)
August 1-6, 1774 resolutions by the delegates from the Virginia Association, held in Williamsburg. Included were resolutions in support of Boston following the Boston Tea Party, setting dates for refusing to import any merchandise from Britain or the West Indies, or purchase any slaves from Africa or the West Indies, as well as establishing the procedures for the embargo.